Multifunctional Polyethylene Glycol Triethoxysilane… Dressing Study – A Clinician-Scientist’s Insights and Perspective - Benskin, Linda (Archives of Clinical and Biomedical Research, 2025)
Chen et al. [1], compared two modified polyurethane-based wound dressings (PUE and PUESi), both intended for use in chronic wounds, with a negative control (gauze) and a positive control (PolyMem) via a series of preliminary in vitro and rodent model tests. Future studies may find that one or both of these two new dressings are beneficial. However, the results of this first study cannot be relied upon. Although they exhibited in-depth knowledge of manufacturing techniques, the study designers seem far less familiar with the science of wound healing and with PolyMem wound dressings. This helps explain the flaws in the methods that led to many of their tests not being translatable to real-world settings. In addition, the interpretation of some of the test results is questionable.